2016
DOI: 10.3389/fphys.2016.00624
|View full text |Cite
|
Sign up to set email alerts
|

Pacing Profiles in Competitive Track Races: Regulation of Exercise Intensity Is Related to Cognitive Ability

Abstract: Pacing has been defined as the goal-directed regulation of exercise intensity over an exercise bout, in which athletes need to decide how and when to invest their energy. The purpose of this study was to explore if the regulation of exercise intensity during competitive track races is different between runners with and without intellectual impairment, which is characterized by significant limitations in intellectual functioning (IQ ≤ 75) and adaptive behavioral deficits, diagnosed before the age of 18. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Indeed, when individuals are competing in separate lanes, such as swimming [46][47][48][49][50][51][52][53][54], 400-m track running [55,56], and rowing [57][58][59][60], the adopted pacing behaviour is quite similar to the pacing strategies as predicted in modelling studies [8,9]. The only study reporting a clear deviation from the theoretically optimal pacing strategy in a discipline using separate lanes in their competition focused on intellectual impaired 400-m and 1500-m runners [61], emphasising the importance of the cognitive skills required for optimal pacing regulation. In contrast, when directly competing in the same lane such as in track cycling [62], long-distance running [63,64] and short track speed skating [65][66][67], spontaneous group synchronization of movements seems to occur and pacing behaviour is adjusted drastically by the athletes [68][69][70].…”
Section: Time Trial Competitionsmentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed, when individuals are competing in separate lanes, such as swimming [46][47][48][49][50][51][52][53][54], 400-m track running [55,56], and rowing [57][58][59][60], the adopted pacing behaviour is quite similar to the pacing strategies as predicted in modelling studies [8,9]. The only study reporting a clear deviation from the theoretically optimal pacing strategy in a discipline using separate lanes in their competition focused on intellectual impaired 400-m and 1500-m runners [61], emphasising the importance of the cognitive skills required for optimal pacing regulation. In contrast, when directly competing in the same lane such as in track cycling [62], long-distance running [63,64] and short track speed skating [65][66][67], spontaneous group synchronization of movements seems to occur and pacing behaviour is adjusted drastically by the athletes [68][69][70].…”
Section: Time Trial Competitionsmentioning
confidence: 79%
“…In a longitudinal study for example, elite long track speed skaters distinguished themselves from non-elite skaters throughout their adolescence by a faster development of their pacing strategy towards the pacing strategies as used in elite 1500-m speed skating competitions [42]. Furthermore, athletes with an intellectual impairment appeared to have difficulties to efficiently self-regulate their pace [61,141], emphasising the cognitive resources that are required in the regulation of exercise intensity.…”
Section: Discussionmentioning
confidence: 99%
“…These factors, along with personal goals and the likely demands of the task are often used to inform the type of pacing strategy adopted by athletes (Smits et al, 2014 ), and research has shown that pacing ability and performance on a physical task are related. For example, Van Biesen et al ( 2016 ) examined the pacing ability of elite runners with mild intellectual impairment to better understand the role that intellectual capacity plays in running. The pacing ability of well-trained runners with and without intellectual impairment was compared during a 400- and 1,500-meter track race.…”
Section: Endurance Tasksmentioning
confidence: 99%
“…However, this may lead to earlier fatigue and steady decrease in pace (34). In addition, for an athlete to maintain his/her predetermined pacing strategy, internal factors such as the existing energy stores, hydration level, neuromuscular fatigue, cardiorespiratory performance, external factors such as the convenience of the race track and environmental conditions and also decision-making processes such as psychological readiness, mental competence, tactical changes, effort perception, nationality, psycho-biological status, and behavioral characteristics play an important role (3,8,13,25,26,28,36). Therefore, it is stated that it is more appropriate to use the concept of pace profile instead of pacing strategy in studies related to pace profiles (31).…”
Section: Issn: 2147-5652mentioning
confidence: 99%